Evaluation of tumor stroma ratio in stage I to IV colorectal carcinoma at a tertiary care hospital in the Morang district, Nepal - Karki, Diksha; Yadav, Pooja; Parajuli, Surya Bahadur (Journal of Biomedical Sciences, 2024)
Background: The tumor stroma ratio has previously been shown to be a strong prognostic factor in colorectal carcinoma. It correlates with high-risk parameters like tumor stage, lymph node metastasis, and lymphovascular invasion. The present study aimed to analyze the tumor stroma ratio (TSR) in Stage I to Stage IV colorectal cancer and correlate it with tumor stage, lymphovascular invasion, and lymph node metastasis. Material and methods: A total of 50 patients whose resection specimens had been received in the Department of Pathology, Birat Medical College Teaching Hospital, Nepal, during the study period. 8 cases who had neo-adjuvant chemotherapy were excluded. The invasive front of the tumor was evaluated using a 10x objective for the stroma percentage and was categorized into the high stroma (>50%) and low stroma (≤50%) TSR. Results: Of 42 cases, 19 (45.2%) tumors have a low tumor stroma ratio, and 23(54.8%) show a high tumor stroma ratio. The low TSR is strongly associated with the high pathological stage of the tumor (p <0.001) and the high lymph node stage (p <0.001). Low TSR tumors were more common on the left side (p <0.001). Lymphovascular invasion is associated with high stroma compared to low stroma (p <0.001). The increasing tumor stage from I to IV strongly correlated with the TSR (p <0.001). Conclusion: The current study confirms the significant association between TSR and the corresponding tumor stage, metastasis in the lymph node, and lymphatic and vascular invasion.